Avaliação e comparação de diferentes comprimentos de onda (660 e 808 nm) da terapia por fotobiomodulação a laser na atrofia muscular em modelo de imobilização em ratos - (:unkn) unknown (Universidade Brasil, 2021)
Atrophy of skeletal striated muscle tissue is a complex process caused by an imbalance between the degradation and synthesis of myofibrillar proteins, leading to a reduction in muscle strength and the quality of life individuals. Considerable efforts have been devoted to establish new treatments for an effective and safe clinical for treatment of muscle atrophy. Among the available therapeutic resources, photobiomodulation therapy (PBMT) has great potential, as it is often used as a promising therapeutic strategy for the rehabilitation of skeletal striated muscle tissue, however, there is no consensus on the best parameters in the treatment of muscle atrophy. Thus, the aim of the present study was to evaluate the in vivo response of PBMT to laser at red and infrared wavelengths in muscle atrophy in an immobilization model in rats. 32 male Wistar rats were used, divided into 4 groups (n = 8): control group (C); Immobilized group (ImC); Immobilized group submitted to PBMT laser at red wavelength (ImR); Immobilized group submitted to laser PBMT at the infrared wavelength (ImIR). The left hind limb was immobilized in extension for 5 days. For laser PBMT, equipment was used (λ = 660 and 808 nm; P = 30 mW; t = 47 s; D = 50 J/cm²) applied at two points in the gastrocnemius muscle (cranial and caudal). Treatments started immediately after removal of the immobilization, with 24-hour intervals, totaling 9 sessions. To evaluate and compare the treatments, histological analysis were performed, as well as the profile area, cell density and ATPase histochemistry. Histological results showed fibers of varied shape, infiltration of inflammatory cells, and thickening of the connective tissue, reduced profile and increased density of muscle fibers in all immobilized animals. Furthermore, it was possible to verify a modulation of the inflammatory process and a lesser thickening of the intramuscular connective tissue in both ImR and ImIR groups, however, these results were more pronounced in the ImIR group, associated with morphological findings of regenerating fibers and an increase in the number of fibers oxidative (type I fibers). Thus, we can conclude that laser PBMT at both wavelengths were effective in changing the morphology of the gastrocnemius muscle subjected to atrophy in an experimental immobilization model, reducing the inflammatory infiltrate and the formation of intramuscular connective tissue. However, RI promoted a more evident positive effect by increasing regenerating muscle fibers and the number of oxidative fibers, which may be a promising resource in the clinical treatment of muscle atrophy.
Keywords: Terapia de fotobiomodulação; Laser de baixa intensidade; Atrofia muscular; Imobilização; Engenharia Biomédica (Bioengenharia)